An Investigation into Major Sheep Diseases and Management Practices in North Shewa Zone, Oromia, Ethiopia - Tadesse Birhanu; Tesfaye Debelu; Said Muhammed; Fikiru Getachew (Veterinary Medicine International)
Sheep have many advantages over large ruminants for most smallholder farmers: lower feed costs, quicker turnover, easy management, and appropriate size at slaughter can be mentioned. They produce in a wide range of agroecologies, from arid lowlands to extremely cool highlands. However, their productivity is hindered by disease burden and poor management practices. In the study area, information on the disease of sheep and related management practices is lacking. Thus, the study aimed to determine the major sheep diseases and management practices in North Shewa Zone, Oromia, Ethiopia. A cross-sectional study design was used from October 2020 to July 2021 in the zone. A multistage sampling technique was used to select study districts and their respective kebeles, while the households were purposively selected. Questionnaire survey, in-depth interview, and physical clinical examination were conducted. A total of 400 households were involved in this study, a majority (32.8%) of whom were illiterates. Ovine pasteurellosis (55.8%) was the major bacterial disease in highlands, whereas sheep pox (54.5%) was the most challenging viral disease in the area. Mange mites (41.3%) were the major parasitic disease. The design of houses was medium (34.5%) which were bedded using sand floor (79.8%) and grass (5.75%), but the drainage system of the house was poorly designed (46.8%) in highlands. A majority of the owners (67.3%) used traditional medicines for the treatment of sheep disease. This study concluded that the burden of the diseases was higher and the management practices were poor in the area, deteriorating the economic benefit of farmers from sheep production. Thus, it urges for operating technical interventions.